2021
DOI: 10.1088/1752-7163/ac15ea
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics study on biomarker and pathway discovery of chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a common heterogeneous respiratory disease characterized by persistent and incompletely reversible airflow limitation. Due to the heterogeneity and phenotype complexity of COPD, traditional diagnostic methods can only provide limited information on predicted results and treatment, which are not sufficient for accurate diagnosis and evaluation. With the development of omics technologies in recent years, genomics, proteomics and metabolomics are widely used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In particular, this method presents poor patient compliance for people with underlying diseases and acute exacerbations. Currently, there is a deficiency in reliable genes or protein biomarkers to assess the diagnosis of COPD. ,, In contrast, metabolite biomarkers function as direct indicators of biochemistry activity, closely correlating the phenotype of disease . Here, we developed PdPt alloy-assisted LDI MS for the effective extraction of metabolic fingerprints in plasma due to the unique physiochemical property and porous structure.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In particular, this method presents poor patient compliance for people with underlying diseases and acute exacerbations. Currently, there is a deficiency in reliable genes or protein biomarkers to assess the diagnosis of COPD. ,, In contrast, metabolite biomarkers function as direct indicators of biochemistry activity, closely correlating the phenotype of disease . Here, we developed PdPt alloy-assisted LDI MS for the effective extraction of metabolic fingerprints in plasma due to the unique physiochemical property and porous structure.…”
Section: Results and Discussionmentioning
confidence: 99%
“…KEGG analysis also identified aminoacyl-tRNA biosynthesis and glycine, serine, and threonine pathway overrepresentation in the metSS, which suggests disturbances in general amino acid metabolism. Aminoacyl-tRNAs are vital for protein synthesis and have been associated with oxidative stress [ 5 , 6 , 26 ]. Similarly, multiple studies have found enrichment of the glycine, serine, and threonine metabolism pathways, which have been associated with COPD exacerbation severity [ 4 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method provides high sensitivity and specificity, frequently eliminating the need for sample derivatization. It is particularly suitable for investigating thermally unstable molecules that are not safe for GC-MS-based methodologies [ 17 ].…”
Section: Analytical Techniques In Metabolomicsmentioning
confidence: 99%